[INVITED] Ultrafast laser micro- and nano-processing with nondiffracting and curved beams: Invited paper for the section : Hot topics in Ultrafast Lasers. (June 2016) - Courvoisier, F.; Stoian, R.; Couairon, A.
Abstract: Ultrafast laser materials processing has undergone an important change with the development of non-diffracting beams. These beams enable overcoming many of the difficulties usually encountered with standard Gaussian-beam focusing in materials. We review the techniques of non-diffracting and accelerating beam shaping that generates lines, tubes or curved segments of focused light on distances that exceed the Gaussian Rayleigh range by several orders of magnitude. We review the benefits and applications of nondiffracting beams for laser micro- and nano-processing in the general context of materials processing with ultrashort pulses in the filamentation regime. We highlight applications on ultra-high aspect ratio nano-drilling and direct laser processing along curves. Abstract : Highlights: We review ultrafast laser processing with nondiffracting and accelerating beams. Nondiffracting beams allow ultra-high aspect ratio laser drilling in single shot. Curved edge profiling and cutting is enabled by accelerating beams.